PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN IPAS SISWA SEKOLAH DASAR - Dian Juli Lestari; M. Jaya Adi Putra; Zufriady (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop Augmented Reality (AR)-based learning media for IPAS subjects for elementary school students. The method used in this study is the Research and Development (R&D) method with a 4D development model consisting of 4 stages Define, Design, Development, and Disseminate. Validation by subject matter experts and media experts yielded an Aiken's V index of 0.91, categorized as highly valid. The one-on-one trial yielded satisfactory interview results from students, who found the learning media provided to be interesting and easy to understand. The limited trial yielded an average score of 83%, categorized as highly positive, and teacher responses yielded a percentage of 86%, also categorized as highly positive. This learning media is effective based on the results of the pretest-posttest measured using the N-Gain Score formula, which obtained a value of 0.68 with a moderate category in the one-on-one trial test and a value of 0.78 with a high category in the limited trial test. The learning media, which has been validated and deemed suitable for printing, has been submitted to SDIT Raudhatur Rahmah. Additionally, the media has been disseminated through the researcher's TikTok social media account to expand its reach. Thus, it can be concluded that the AR-based learning media for the IPAS subject for students at this school is valid and can be used in the learning process.